0+10*1-60-60*10+10=

Simple and best practice solution for 0+10*1-60-60*10+10= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0+10*1-60-60*10+10= equation:


Simplifying
0 + 10 * 1 + -60 + -60 * 10 + 10 = 0

Multiply 10 * 1
0 + 10 + -60 + -60 * 10 + 10 = 0

Multiply -60 * 10
0 + 10 + -60 + -600 + 10 = 0

Combine like terms: 0 + 10 = 10
10 + -60 + -600 + 10 = 0

Combine like terms: 10 + -60 = -50
-50 + -600 + 10 = 0

Combine like terms: -50 + -600 = -650
-650 + 10 = 0

Combine like terms: -650 + 10 = -640
-640 = 0

Solving
-640 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7+3(2n+6)-n= | | 8b-64a=8 | | 11x=286 | | 3(4x-6)+18= | | 2x-1=14-x | | 4z+3=6+2z | | 21-n+36= | | m+60=m+303 | | m+60=p+303 | | 6x-16=32 | | 5x+9=5+3x | | l=90(0+m)-3 | | 60=10p | | -7=117 | | 12-25+6=177 | | 3(x+2)-2(x-1)=7 | | y-21/3=-3 | | 85-79=27y-33y | | -n=5 | | x-6=34+34+3x | | x-6=34+34 | | -s=9 | | 2.3=x-5.9 | | x-6=34+x | | 39=z+51 | | 2d=5d-60 | | 5x+(-4)=36 | | 2D=0 | | -11=z-4 | | -2x-45=34+56 | | 4x-3+2x=8x-3-x | | -4(2p+4)-40=2(4p+4) |

Equations solver categories